Estimating the potential health effects of cleaner air in the initial stages of the COVID-19 pandemic: a study in Malmö, Sweden - Ebba Malmqvist; Emilie Stroh; Erin Flanagan; Christina Isaxon; Pontus Roldin; Anna Oudin (Taylor & Francis Group, 2024)
Background During the initial phase of the COVID-19 pandemic, reductions in air pollution were globally observed owing to decreased human activities, underscoring the potential for cleaner air through shifts in human behaviour. Objectives The objective of the present study was to hypothetically estimate the resulting population health impacts in Malmö, Sweden, if these improvements in air quality were to become permanent. Methods We utilized air pollution data from two measurement campaigns conducted in the spring of 2019 and the spring of 2020 for our Health Impact Assessment, applying standard methods. This assessment involved making assumptions about baseline population risk and using established concentration-response functions. Results In the spring of 2020, the NO2 concentrations exhibited an average decrease of 6.6 μg/m3 (42%) decrease and PM2.5 concentrations a 1.9 μg/m3 (22%) decrease, compared to the spring of 2019. If sustained, such improvements could lead to an estimated 1-3% decrease in premature deaths, a 2% decrease in preeclampsia cases, a 6% decrease in low birthweight children, a 4% decrease in bronchitis cases among children, a 2% decrease in asthma cases, a 0.2% decrease in hospital admissions for respiratory diagnoses, and an estimated 11% decrease in dementia cases annually. Conclusion The findings illustrate the potential for enhanced health in Malmö due to improved air quality. Efforts to combat air pollution and implement long-term strategies, such as those targeting urban mobility and commuting patterns, are essential for the health and well-being of both local and global populations.